Performance Review of Crumb Rubber as A Modifier in Asphalt Pavement - INTAN JASMIN ROSLI; SARIF , ABD SUKOR (Progress in Engineering Application and Technology, 2021)
The rising number of wheeled transportation has led to an increasing waste tyre in the country. Thus, it is always experiencing pavement failure such as cracking, potholes, depression, and raveling, which bring uncomfortable feelings to road users. Therefore, the modified pavement is needed for solving these problems by adding crumb rubber to the asphalt mixture. In this study, the crumb rubber from previous studies was used to determine the performance of crumb rubber as a modifier in asphalt pavement. Six crumb rubber-modified pavement data consist of 8%, 10%, and 12%, with the different bitumen grades (PEN 60-70, PEN 70-80, and PEN 80-100) prepared and analyzed. The laboratory testing of Penetration Test, Softening Test, and Ductility Test found the most suitable bitumen grade used in Malaysia is PEN 60-70. Besides, the Marshall Stability test and Indirect Tensile Strength test are performed and indicate that 10% is the optimum percentage of crumb rubber added in the mixture. Hence, the study found that the addition of crumb rubber in asphalt pavement can improve the pavement’s strength, quality, and performance.